Cooperative action of the paralogous maize lateral organ boundaries (LOB) domain proteins RTCS and RTCL in shoot‐borne root formation. Issue 4 (22nd April 2015) - Xu, Changzheng; Tai, Huanhuan; Saleem, Muhammad; Ludwig, Yvonne; Majer, Christine; Berendzen, Kenneth W.; Nagel, Kerstin A.; Wojciechowski, Tobias; Meeley, Robert B.; Taramino, Graziana; Hochholdinger, Frank
Summary: The paralogous maize ( Zea mays ) LBD ( Lateral Organ Boundaries Domain ) genes rtcs ( rootless concerning crown and seminal roots ) and rtcl ( rtcs‐like ) emerged from an ancient whole‐genome duplication. RTCS is a key regulator of crown root initiation. The diversity of expression, molecular interaction and phenotype of rtcs and rtcl were investigated. The rtcs and rtcl genes display highly correlated spatio‐temporal expression patterns in roots, despite the significantly higher expression of rtcs . Both RTCS and RTCL proteins bind to LBD downstream promoters and act as transcription factors. In line with its auxin inducibility and binding to auxin response elements of rtcs and rtcl promoters, ARF34 (AUXIN RESPONSE FACTOR 34) acts as transcriptional activator. Yeast two‐hybrid screening combined with bimolecular fluorescence complementation (BiFC) experiments revealed conserved and unique interaction partners of RTCS and RTCL. The rtcl mutation leads to defective shoot‐borne root elongation early in development. Cooperative action of RTCS and RTCL during shoot‐borne root formation was demonstrated by rtcs ‐dependent repression of rtcl transcription in coleoptilar nodes. Although RTCS is instrumental in shoot‐borne root initiation, RTCL controls shoot‐borne root elongation early in development. Their conserved role in auxin signaling, but diverse function in shoot‐borne root formation, is underscored by their conserved and unique interaction partners.